Rapes in India during 1991-2014 - P Gopala Sarma (Telangana Journal of Psychiatry, 2016)
Background: Increasing reports of rapes and responsibilities of clinicians. Objective: To analyse rape in preteens, adolescents and adults in India over a period of two plus decades. Methods: Rape rate was computed from National Crime Records Bureau of India crime data and US Census Bureau International population census statistics for the age groups- 0-12 (Preteen), 13-18 (Adolescent) and above 18 (Adults) for the period 1991-2014. Rate was computed and trend plotted. Results: The total rape victims during the index period were 432847 averaging 18819. There were a total of 43520 preteen, 102833 adolescent and 286494 adult rape victims in the index period averaging 1892, 4471 and 12456 per annum respectively. The linear trend line indicates an increase in adolescent and adult group and almost stationary in preteens. Conclusions: As rape rate is high in adolescents and adults and is on the raise, there is an urgent need for strategic planning in detecting, treating, and de-stigmatizing the act.